2015
DOI: 10.1063/1.4915091
|View full text |Cite
|
Sign up to set email alerts
|

Note: Self-biased magnetic field sensor using end-bonding magnetoelectric heterostructure

Abstract: A high sensitivity magnetic field sensor based on magnetoelectric (ME) coupling is presented. The ME sensor FeCuNbSiB/Nickel-PZT-FeCuNbSiB/Nickel is made by bonding magnetization-graded magnetostrictive materials FeCuNbSiB/Nickel at the free ends of the piezoelectric Pb(Zr1-x,Tix)O3 (PZT) plate. Experiments indicate that the proposed sensor has a zero-bias field sensitivity of 14.7 V/Oe at resonance, which is ∼41.6 times larger than that of previous FeCuNbSiB-PZT-FeCuNbSiB. Furthermore, without external biased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
6
1
1
Order By: Relevance
“…Using the magnetization-graded ferromagnetic materials, a large piezomagnetic coefficient at zero-biased field can be obtained. [16][17][18] The dimensions of terfenol-D plate and FeCuNbSiB foil were 12 × 6 × 0.8 mm 3 (l × w × t) and 12 × 6 × 0.025 mm 3 (l × w × t), respectively. The magnetostrictive layers (terfenol-D and FeCuNbSiB) were magnetized along the longitudinal direction.…”
Section: Methodsmentioning
confidence: 99%
“…Using the magnetization-graded ferromagnetic materials, a large piezomagnetic coefficient at zero-biased field can be obtained. [16][17][18] The dimensions of terfenol-D plate and FeCuNbSiB foil were 12 × 6 × 0.8 mm 3 (l × w × t) and 12 × 6 × 0.025 mm 3 (l × w × t), respectively. The magnetostrictive layers (terfenol-D and FeCuNbSiB) were magnetized along the longitudinal direction.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the laminate composites consisting of magnetostrictive and piezoelectric materials provide high ME effects [1][2][3][4][5][6], offer potential applications in magnetic field sensors [7][8][9][10] and ME transducers [11,12]. The experimental and analytical results on ME laminates have shown that the ME composites exhibit significant ME effects only near an optimum bias magnetic field (H dc ) [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 95%
“…The experimental and analytical results on ME laminates have shown that the ME composites exhibit significant ME effects only near an optimum bias magnetic field (H dc ) [1][2][3][4][5][6][7][8][9][10]. Hence, achieving self-biased ME effect has become of great research interest recently [12][13][14].…”
Section: Introductionmentioning
confidence: 95%
“…Due to the bonding of a magnetization-graded FeCuNbSiB/Ni layer to the free end of a piezoelectric PZT plate, a broadband SME structure with a high peak value, namely, FeCuNbSiB/ (Ni-PZT-Ni)/FeCuNbSiB, was built (Figure 7B). 177,178 With a magnetization-graded layer and end-bonding design, the α SME of FeCuNbSiB/Ni/PZT/FeCuNbSiB/Ni structures reached 183.2 V cm −1 Oe −1 . Due to the end-bonding design, the adverse effects of the interface layer between the magnetostrictive and piezoelectric phases were reduced, resulting in the enhancement of ME coupling.…”
Section: Broadband Sme Effectmentioning
confidence: 99%